SYN-006, a Novel Carbapenemase, Intended to Protect the Gut Microbiome from Antibiotic-Mediated Damage May Also Reduce Propagation of Carbapenem-Resistant Pathogens. (4th October 2017) - Kaleko, Michael; Furlan-Freguia, Christian; Subramanian, Poorani; Hasan, Nur A; Colwell, Rita R; Connelly, Sheila
Abstract: Background: Β-lactam antibiotics that are excreted in bile can damage the gut microbiota, leading to serious adventitious infections and propagation of antibiotic resistance. SYN-004 (ribaxamase) is a β-lactamase intended for oral use with certain IV β-lactam antibiotics to degrade the antibiotic in the GI tract to protect the microbiome. Ribaxamase was evaluated in a phase 2b clinical study that met its primary endpoint of significantly reducing C. difficile infection in patients treated with ceftriaxone. Ribaxamase degrades penicillins and cephalosporins, but not carbapenems. SYN-006, a carbapenemase, was identified to expand this prophylactic approach to all classes of β-lactam antibiotics. Methods: SYN-006, a metallo-β-lactamase derived from B. cereus, is produced in E. coli . Antibiotic degradation was assessed using a bacterial growth assay. SYN-006 (1 mg/kg, PO) was delivered to fistulated dogs that received the carbapenem, meropenem (30 mg/kg, IV). Blood and intestinal antibiotic levels were assessed. A pig model of carbapenem-mediated microbiome disruption was established with microbiome and resistome analysis performed using fecal DNA using whole genome shotgun sequence data. Results: In vitro, SYN-006 displayed a broad antibiotic degradation profile that included carbapenems, cephalosporins, and penicillins, and was resistant to β-lactamase inhibitors. SYN-006 degraded meropenem in the GI tract of dogs without affecting systemic antibiotic levels. In pigs, ertapenem significantly changed the composition of the gut microbiome and mediated emergence and propagation of a wide range of antibiotic resistance genes, including extended spectrum β-lactamase genes such as the carbapenemase gene, IMP-27. Conclusion: SYN-006 efficiently degraded all classes of β-lactam antibiotics including carbapenems in vitro, and meropenem within the dog GI tract. The pig model of carbapenem-mediated microbiome disruption is intended to be used to evaluate the ability of SYN-006 to protect the gut microbiome and attenuate antibiotic resistance. SYN-006 has the potential to protect the gut microbiome from all classes of β-lactam antibiotics and to reduce the emergence of carbapenem-resistant pathogens. Disclosures: M. Kaleko, Synthetic Biologics, Inc.: Employee and Shareholder, Salary and stock options.C. Furlan-Freguia, Synthetic Biologics, Inc.: Employee and Shareholder, Salary and Stock Options. P. Subramanian, CosmosID, Inc.: Employee, Salary. N. A. Hasan, CosmosID, Inc.: Employee, Salary. R. R. Colwell, CosmosID, Inc.: Employee, Salary. S. Connelly, Synthetic Biologics, Inc.: Employee, Salary